A decade of academic merit decline: policy and institutional practices in conferring honorary professorships at Indonesian universities (2014–2024) - Naimatul Chariro; Wani Maler; Desy Fitriana; Ikomatussuniah Ikomatussuniah; Moh Mudzakkir (Department of Government Studies, Universitas Muhammadiyah Makassar, 2025)
This study examines the dynamics of policy and institutional practices in conferring honorary professorships in Indonesian higher education institutions from 2014 to 2024. Using qualitative document analysis, it critically analyzes regulatory frameworks, institutional decision-making processes, and the competing institutional logics—drawing explicitly on the Institutional Logics Perspective—that shape the awarding of honorary professorships. The findings reveal a sharp rise in the conferral of honorary titles following the issuance of Ministry of Education and Culture Regulation No. 38/2021. However, the practice remains dominated by political rather than academic considerations, as most recipients are politicians or public officials, reflecting the influence of political and market logics over academic and professional standards. The study also highlights regulatory ambiguities and weak enforcement mechanisms that facilitate transactional practices and undermine institutional credibility, alongside persistent gender disparities marked by the limited representation of female recipients. The research argues for a critical reassessment of existing regulations and stronger, transparent, and academically grounded procedures. Its findings contribute to broader discussions on higher education governance in Indonesia and offer conceptual relevance for international debates on honorary titles, especially regarding tensions between academic integrity, institutional reputation, and political influence. The study calls for universities to balance public image considerations with academic merit to ensure that honorary professorships reflect genuine contributions to science, education, and society.